2010
DOI: 10.1128/jvi.02087-09
|View full text |Cite
|
Sign up to set email alerts
|

Immune Evasion Proteins of Murine Cytomegalovirus Preferentially Affect Cell Surface Display of Recently Generated Peptide Presentation Complexes

Abstract: For recognition of infected cells by CD8 T cells, antigenic peptides are presented at the cell surface, bound to major histocompatibility complex class I (MHC-I) molecules. Downmodulation of cell surface MHC-I molecules is regarded as a hallmark function of cytomegalovirus-encoded immunoevasins. The molecular mechanisms by which immunoevasins interfere with the MHC-I pathway suggest, however, that this downmodulation may be secondary to an interruption of turnover replenishment and that hindrance of the vesicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 98 publications
2
55
0
Order By: Relevance
“…Notably, m04, which so far did not show a convincing inhibitory function, appears to help m06 and m152 in downmodulating MHC-I cell surface expression (Fig. 1b, Target cell conditioning by IFN-c almost levels the differences in antigen presentation imposed by vRAPs As we have shown previously, downmodulation of total cell surface MHC-I expression by the combined action of vRAPs m06 and m152 results primarily from blocking the trafficking of recently loaded pMHC-I complexes to the cell surface, leading to a lack of resupply of MHC-I molecules in the otherwise constitutive MHC-I turnover [54] (see also the accompanying review article by Lemmermann et al in this issue of MMI). This predicts the patterns of vRAP function in cell surface presentation of defined pMHC-I complexes and their recognition by cognate CD8 T cells follow the patterns seen for total MHC-I cell surface expression (which actually includes MHC-I molecules loaded with self-peptides or peptides from unrelated antigens).…”
Section: Pre-treatment Of Cells With Ifn-c Moderates the Effect Of Vrmentioning
confidence: 69%
See 1 more Smart Citation
“…Notably, m04, which so far did not show a convincing inhibitory function, appears to help m06 and m152 in downmodulating MHC-I cell surface expression (Fig. 1b, Target cell conditioning by IFN-c almost levels the differences in antigen presentation imposed by vRAPs As we have shown previously, downmodulation of total cell surface MHC-I expression by the combined action of vRAPs m06 and m152 results primarily from blocking the trafficking of recently loaded pMHC-I complexes to the cell surface, leading to a lack of resupply of MHC-I molecules in the otherwise constitutive MHC-I turnover [54] (see also the accompanying review article by Lemmermann et al in this issue of MMI). This predicts the patterns of vRAP function in cell surface presentation of defined pMHC-I complexes and their recognition by cognate CD8 T cells follow the patterns seen for total MHC-I cell surface expression (which actually includes MHC-I molecules loaded with self-peptides or peptides from unrelated antigens).…”
Section: Pre-treatment Of Cells With Ifn-c Moderates the Effect Of Vrmentioning
confidence: 69%
“…Response of all CD8 T cells of a polyclonal cell population is thus a threshold phenomenon that indicates nothing more than presentation of pMHC-I complexes sufficient for sensitizing all CD8 T cells characterized by a particular functional avidity (and TCR structural avidity) distribution, whereas the actual number of pMHC-I complexes on the cell surface of the stimulating infected cells may still differ widely in the absence or presence of vRAPs. Evidence in support of this possibility has been provided by a direct quantitation of pMHC-I (SIINFEKL-K b ) complexes with an antibody specific for this particular complex [54] (see also the accompanying review by Lemmermann et al in this issue of MMI). Functional evidence is also provided by taking into account the intensity of CD8 T-cell sensitization that is indicated by the amounts of IFN-c secreted during the ELISpot assay, which are reflected by spot sizes.…”
Section: Pre-treatment Of Cells With Ifn-c Moderates the Effect Of Vrmentioning
confidence: 95%
“…Both viruses encode the SIINFEKL peptide but MCMV-3DΔvRAP lacks the “ v iral r egulator of a ntigen p resentation” genes encoding for the MHC class I evasion proteins gp48/m06 and gp40/m152 [53], [54]. In contrast to MCMV-3D, this mutant is therefore expected to lack the ability to interfere with MHC class I peptide surface expression as was recently shown for a related virus mutant [55]. We speculated that MHC class I bound SIINFEKL peptide presentation on MCMV-3DΔvRAP-infected cells would allow direct recognition of infected cells by OTI T cells and decreased luciferase activity in organs of these animals would be an in vivo indicator for the activity of cytotoxic T lymphocytes (CTL).…”
Section: Resultsmentioning
confidence: 93%
“…Lemmermann et al (18) showed that the immune evasion proteins from murine cytomegalovirus preferentially affect cell surface display of recently generated peptide presentation complexes. These immunoevasins only slowly downmodulate preexisting cell surface MHC-I/peptide complexes, which is a passive mechanism due to constitutive turnover in the absence of resupply.…”
Section: Discussionmentioning
confidence: 99%